Austerity and the Labor Movement - Schiavone, Michael (Book collections on Project MUSE., 2017)
"Austerity policies have become the new norm throughout both the developed and developing world. Indeed, austerity has become the new buzz word in the lexicon of politicians from across the political spectrum. At the same time austerity measures have been met with mass protest, the most famous example of which is the Occupy Movement. In the not-too-distant past it would have been the labor movement at the forefront resisting policies that arguably disproportionally target working people and their families. Throughout the twentieth century it was the labor movement that fought for all working people. However, there is an increasing assumption that the labor movement is unable to adequately defend workers from the onslaught of austerity measures. Austerity and the Labor Movement analyzes whether this assumption is indeed true. Examining the labor movements in the US, UK, Greece, Ireland, and Spain, Michael Schiavone provides a systematic explanation of the appeal of austerity policies in certain circles and why the labor movement in each of these countries has been largely unsuccessful in overturning such policies. He argues that the labor movement needs to make major changes and embrace social movement unionism if it has any hope to stop its decline and have any chance to successfully fight against austerity and neoliberalism more generally"--